NMR Study of Methyl β-orsellinate from Dirinaria sp. was Collected from Coastal Areas of Teluk Nipah, Pulau Pangkor, Perak Malaysia - Andi Rifki Rosandy; Nurul Nadiah Binti Abdul Rahman; Rozida Khalid; Agus Chahyadi; Elfahmi Elfahmi (Acta Pharmaceutica Indonesia, 2021)
The research was carried out to isolate and characterize the methyl β-orsellinate of lichen Dirinaria sp. collected from the coastal areas of Teluk Nipah, Pulau Pangkor, Perak Malaysia. The sample was extracted in methanol for three times at room temperature. Subsequently, the crude extracts and further analysed using thin-layer chromatography (TLC) and vacuum liquid chromatography (VLC). To derive the pure compounds, the isolation step was performed using radial chromatography (RC). The chemical structure of the isolated compound was determined by several spectroscopies i.e. infra-red (IR), nuclear magnetic resonances (NMR), and mass spectrometric (MS). The compound was identified as methyl β-orsellinate.